Predicting Long-Term Respiratory Outcomes in Premature Infants: Is It Time to Move beyond Bronchopulmonary Dysplasia? - Deepak Jain; Alexander Feldman; Subhasri Sangam (MDPI AG, 2020)
Premature birth has been shown to be associated with adverse respiratory health in children and adults; children diagnosed with bronchopulmonary dysplasia (BPD) in infancy are at particularly high risk. Since its first description by Northway et al. about half a century ago, the definition of BPD has gone through several iterations reflecting the changes in the patient population, advancements in knowledge of lung development and injury, and improvements in perinatal care practices. One of the key benchmarks for optimally defining BPD has been the ability to predict long-term respiratory and health outcomes. This definition is needed by multiple stakeholders for hosts of reasons including: providing parents with some expectations for the future, to guide clinicians for developing longer term follow-up practices, to assist policy makers to allocate resources, and to support researchers involved in developing preventive or therapeutic strategies and designing studies with meaningful outcome measures. Long-term respiratory outcomes in preterm infants with BPD have shown variable results reflecting not only limitations of the current definition of BPD, but also potentially the impact of other prenatal, postnatal and childhood factors on the respiratory health. In this manuscript, we present an overview of the long-term respiratory outcomes in infants with BPD and discuss the role of other modifiable or non-modifiable factors affecting respiratory health in preterm infants. We will also discuss the limitations of using BPD as a predictor of respiratory morbidities and some of the recent advances in delineating the causes and severity of respiratory insufficiency in infants diagnosed with BPD.